A trial‐based cost‐effectiveness analysis of topical 5‐fluorouracil vs. imiquimod vs. ingenol mebutate vs. methyl aminolaevulinate conventional photodynamic therapy for the treatment of actinic keratosis in the head and neck area performed in the Netherlands. (19th February 2020) - Jansen, M.H.E.; Kessels, J.P.H.M.; Merks, I.; Nelemans, P.J.; Kelleners‐Smeets, N.W.J.; Mosterd, K.; Essers, B.A.B.
Summary: Background: Actinic keratosis (AK) is a common premalignant skin condition that might have the ability to progress into squamous cell carcinoma. Due to the high incidence of AK, treatment of this disease significantly impacts healthcare spending. Objectives: To determine which commonly prescribed field‐directed treatment is the most cost‐effective, when comparing 5‐fluorouracil (5‐FU) 5%, imiquimod (IMQ) 5%, ingenol mebutate (IM) 0·015% and methyl aminolaevulinate photodynamic therapy (MAL‐PDT) for AK in the head and neck region. Methods: We performed an economic evaluation from a healthcare perspective. Data were collected alongside a single‐blinded, prospective, multicentre randomized controlled trial with 624 participants in the Netherlands. The outcome measure was expressed as the incremental cost‐effectiveness ratio, which is the incremental costs per additional patient with ≥ 75% lesion reduction compared with baseline. This trial was registered at ClinicalTrials.gov, number NCT02281682. Results: The trial showed that 5‐FU was the most effective field treatment for AK in the head and neck region. Twelve months post‐treatment, the total mean costs for 5‐FU were significantly lower (€433) than the €728, €775 and €1621 for IMQ, IM and MAL‐PDT, respectively. The results showed that 5‐FU was a dominant cost‐effective treatment (more effective and less expensive) compared with the other treatments, 12 months post‐treatment. Conclusions: Based on these results, we consider 5‐FU 5% cream as the first‐choice treatment option for multiple AKs in the head and neck area. What's already known about this topic? Due to the increasing incidence of actinic keratosis (AK), the recommended treatment results in a considerable socioeconomic burden for (dermatological) healthcare. Although cost‐effectiveness modelling studies have been performed in which different treatments for AK were compared, a prospective clinical trial comparing four frequently prescribed treatments on effectiveness and resource consumption within a time horizon of 12 months has never been conducted. What does this study add? This is the first study examining the cost‐effectiveness of 5‐fluorouracil 5% cream, imiquimod 5% cream, ingenol mebutate 0·015% gel and methyl aminolaevulinate photodynamic therapy, with data collected in a randomized controlled trial over a time horizon of 12 months. We found that 5‐fluorouracil was a dominant cost‐effective treatment (more effective and less costly), based on data from the Netherlands. Linked Comment: Steeb et al. Br J Dermatol 2020; 183 :612 . Abstract : Linked Comment: Steeb et al. Br J Dermatol 2020; 183 :612 . Plain language summary available online